Providing Health Education as an Effort to Improve Knowledge and Prevention of COVID-19 for Persons with Disabilities, PPDMS Social Institutions, Nglipar, Gunungkidul - The Maria Meiwati Widagdo; Widya Christine Manus; Frista Frista; Matahari Bunga Indonesia (LPPM Universitas Ma Chung, 2022)
People with disabilities are vulnerable to being infected with the COVID-19 virus. The COVID-19 pandemic has had an impact on human life, including the health of people with disabilities. The government makes various policies and programs in an effort to prevent the spread of COVID-19, but their implementation is still challenging for people with disabilities. This community service program was carried out in collaboration with Mitra Sejahtera Disability Empowerment Center (PPDMS), an organization empowering people with disabilities in Gunungkidul Regency. Empowerment of people with disabilities was carried out using 'community control' principle in which the community has the control in making decisions regarding the problems they face so that they can adopt a ‘new normal’ lifestyle because of their knowledge. The principle of 'community control' was applied by providing education about COVID-19 situation in Indonesia, the symptoms and signs of COVID-19 infection, wash hands, proper cough etiquette, how to use masks, food and lifestyle that can prevent COVID-19 transmission, as well as about the benefits of COVID-19 vaccination. Education was given with a presentation followed by discussion. Evaluation was carried out quantitatively and qualitatively. Quantitative evaluation using pretest and post-test showed an increase in knowledge. Qualitative evaluation using FGD indicated changes in attitudes and behavior that support the adoption of ‘new normal’ lifestyle to prevent transmission of COVID-19. People with disabilities who have received education disseminate the information obtained to other people with disabilities, resulted in multiplication effect of this empowerment program for people with disabilities.